DOI: 10.17077/etd.6ufvkrqf
|View full text |Cite
|
Sign up to set email alerts
|

Use of standardized nursing terminologies in electronic health records for oncology care

Abstract: The purpose of this study was to identify the characteristics of cancer patients and the most frequently chosen nursing diagnoses, outcomes and interventions chosen for care plans from a large Midwestern acute care hospital. In addition the patients' outcome change scores and length of stay from the four oncology specialty units are investigated. Donabedian's structure-process-outcome model is the framework for this study. This is a descriptive retrospective study. The sample included a total of 2,237 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 66 publications
1
1
0
Order By: Relevance
“…This shows the importance of nursing diagnosis in guiding nurses who care for oncology patients with different admission reasons. These results were consistent with the result of a previous retrospective study [ 18 ] that examined nursing diagnoses of 2,237 patients admitted to medical oncology units; they reported an average of 3.1 nursing diagnoses per patient, ranging from 1 to 28 diagnoses during an average length of stay of 3.7 days. Our result also highlights the complexity of patients’ care in medical oncology units, which implies the need to reconsider the nurse–patient ratio in these settings to meet patients’ care demands.…”
Section: Discussionsupporting
confidence: 91%
“…This shows the importance of nursing diagnosis in guiding nurses who care for oncology patients with different admission reasons. These results were consistent with the result of a previous retrospective study [ 18 ] that examined nursing diagnoses of 2,237 patients admitted to medical oncology units; they reported an average of 3.1 nursing diagnoses per patient, ranging from 1 to 28 diagnoses during an average length of stay of 3.7 days. Our result also highlights the complexity of patients’ care in medical oncology units, which implies the need to reconsider the nurse–patient ratio in these settings to meet patients’ care demands.…”
Section: Discussionsupporting
confidence: 91%
“…A descriptive Doctoral study also conducted in the USA explored documentation relating to care in seeking to identify retrospectively from a range of sources the characteristics of cancer patients and the most commonly-selected nursing diagnoses, interventions and outcomes [32]. The study found commonality in the selection of observation and intervention statements, and in linkages between these, although the most com- mon observation and intervention statements may vary between settings.…”
Section: Standardsmentioning
confidence: 99%